Role of third sector in promoting health outcomes in Kerala: a sociological study - O., Mubeena; Akram, Mohammad (International Journal Of Community Medicine And Public Health, 2017)
Third sector is an alternative sector separate from and balancing the state and the market. Third sector refers to different kinds of not-for profit organizations such as charities, Non-Governmental Organizations (NGOs), self-help groups, social enterprises, networks, and clubs. This paper seeks to understand how third sector organizations become important in improving health outcomes in Kerala. Third sectors play very important role in improving health outcomes at several levels. Sometimes they influence health outcomes directly and sometimes through making improvements in other variables like education, sanitation, poverty alleviation, and public awareness programs. The study is based on analytical method and the information is collected from various secondary sources and reviews. The study finds that, in Kerala, several third sector organizations work on varied issue such as, livelihood and poverty, education, improving water supply and sanitation, etc. which ultimately reflect in the health outcome of the state and there are also other organizations which make specific interventions in direct medical care. It also reveals that high level of education and health awareness have sensitized the people to the need for timely health intervention and thus helped to create demand for healthcare. The study further reveals that third sector plays a key role in the promotion of health care, especially at a time when the State is facing an increase in the number of various lifestyle disease cases. An important finding of the study is the fact that Kerala’s highest stocks of social capital promote the existence of the third sector.